2022
DOI: 10.1101/2022.07.13.499896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional landscape of α-synuclein fibril conformations amplified from cerebrospinal fluid

Abstract: Lewy body dementias are pathologically defined by the deposition of α-synuclein fibrils into inclusions throughout the brain. Cerebrospinal fluid (CSF) from cases harbors circulating α-synuclein-fibril seeds, and parental α-synuclein fibrils can template core structure into amplified fibrils. Using cryo-electron microscopy, we identify six novel α-synuclein fibril assemblies amplified from ten CSF samples (3.8 Å to 2.9 Å nominal resolutions). Fibrils are classified based on two types of filament interaction, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Filament assemblies amplified in vitro have also been shown to differ in their seeding behaviour in vivo ( 44 , 45 ). However, known structures of seeded α-synuclein aggregates are different from those of the seeds ( 46 49 ). Unlike for Lewy body diseases, two filament types have been observed in MSA, each of which is made of two different protofilaments ( 6 ).…”
Section: Discussionmentioning
confidence: 98%
“…Filament assemblies amplified in vitro have also been shown to differ in their seeding behaviour in vivo ( 44 , 45 ). However, known structures of seeded α-synuclein aggregates are different from those of the seeds ( 46 49 ). Unlike for Lewy body diseases, two filament types have been observed in MSA, each of which is made of two different protofilaments ( 6 ).…”
Section: Discussionmentioning
confidence: 98%
“…As in the study described earlier, the majority of amplified α-syn filaments were identical to spontaneous recombinant α-syn filaments, and several other filaments identified at low percentages did not show the Lewy fold. The structures of α-syn filaments formed in other SAA studies also differed from those of brain-derived filaments [ 113 - 116 ]. More recently, it has been demonstrated that α-syn in serum from patients with synucleinopathy can be amplified by SAA after immunoprecipitation [ 117 ].…”
Section: α-Syn Filaments In In Vitro Modelsmentioning
confidence: 94%
“…The structures of α-syn filaments formed in other SAA studies also differed from those of brain-derived filaments. [113][114][115][116] More recently, it has been demonstrated that α-syn in serum from patients with synucleinopathy can be amplified by SAA after immunoprecipitation. 117 The ultrastructures of SAA products differed from those of brain-derived filaments, such as straight or twisted protofilaments in MSA-derived products and twisted or bundled filaments in LBD-derived products.…”
Section: α-Syn Filaments In In Vitro Modelsmentioning
confidence: 99%
“…Despite the clear in uence of bril structure on αSyn in vitro and in vivo pathological activity with respect to seeding potency, inclusion morphology, cell tropism, and biophysical signatures, attempts to generate recombinant brils that faithfully recapitulate the properties of brain-derived αSyn aggregates have been met with limited success. Furthermore, even though brain-derived αSyn aggregates can template the brillization of recombinant αSyn, as observed in seeded aggregation assays or protein misfolding cyclic ampli cation-based strategies using brain lysates or cerebrospinal uid, brils generated in this manner remain conformationally and functionally distinct from brain-derived αSyn aggregates [27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%